Pattern of Intussusception on Infants and Children in Dr. Hasan Sadikin Hospital Bandung - Silmina Kusmaheidi; Rizki Diposarosa; Harry Galuh Nugraha (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Intussusception is the most frequent cause of acute intestinal obstruction in infants and toddlers. Incidence was reported at 1.5 to 4 cases for every 1000 live birth. In Dr. Hasan Sadikin General Hospital, Bandung, 55 cases were reported between 2005–2008. This study aimed to identify the characteristics of intussusception patients at Department of Pediatric Surgery Dr. Hasan Sadikin General Hospital, Bandung periode 2009–2011.Methods: This was a retrospective descriptive study by using medical records of intussusceptions patient’s from January 2009 to December 2011. The information collected were age, gender, chief complaint, signs and symptoms, onset of symptoms, nutritional status, history of previous infection, type of intussusceptions, pathologic lead point, and complications; including bowel necrosis and sepsis. The collected data was analyzed and presented as percentages shown in tablesResults: There were 32 cases found, of which 84.4% affected well-nourished infants <1 year. Male was predominant (2:1). Bloody mucous stool was the major chief complaint (84.4%). Accompanying symptoms were pain due to colic, vomiting, bloating, and abdominal mass. Eleven patients were found with the onset of symptoms at ≤24 hours. Thirty-one percent (31%) cases were reported with the history of respiratory tract infection and 44% cases with the history of diarrhea. Most common type found was ileocolic. Pathologic lead point was only found in a single case.Conclusions: Intussusception cases in Dr. Hasan Sadikin General Hospital are decreasing, with the characteristics mainly affect well-nourished children, under 1 year old, predominantly male. The prominent chief complaint is bloody mucous stool, whereas ileocolic is the most common type with history of infection. [AMJ.2015;2(3):458–62] DOI: 10.15850/amj.v2n3.502